Crack-free silicate bioceramics from preceramic polymers. (18th May 2016) - Elsayed, H.; Colombo, P.
Abstract : As a case study, the present paper illustrates an innovative processing method employing a preceramic polymer containing different fillers, which can be used to manufacture various ceramic components for biomedical applications. Crack-free wollastonite (CaSiO3 ) ceramics were successfully produced, with high phase purity, after heating at 900°C in air starting from a silicone resin containing CaCO3 micro-sized particles as 'active filler'. As 'passive filler', wollastonite preceramised powders as well as commercially available wollastonite fibres were added. Their presence reduces the gas evolution occurring due to the decomposition of the calcium carbonate active filler and the polymer-to-ceramic conversion, reducing the stresses that generate in the component during heating. The resulting samples exhibited improvements in terms of the morphology and the mechanical strength, with respect to samples not containing any passive fillers, without significant modification of the final phase assemblage.